The COUNTER Code of Practice for Books and Reference Works – a primer - Shepherd, Peter T.; Woodward, Hazel (United Kingdom Serials Group, 2009)
Release 1 of the COUNTER Code of Practice for Books and Reference Works was published in 2006 and provides an international standard for vendor recording and reporting of the usage of e-books and reference works. By July 2009, 23 vendors were compliant with this Code of Practice. It has much in common with the well-established COUNTER Code of Practice for Journals and Databases but it also has a number of important features that take into account the greater diversity of e-books. This article provides a guide to the Code of Practice for both vendors and librarians, and addresses compliance issues relevant to both groups.